City branding of Palembang: understanding cultural identification through logo and tagline - Rahma Santhi Zinaida; Sunarto Sunarto; Manik Sunuantari (Association for Scientific Computing Electrical and Engineering (ASCEE), 2020)
City branding is believed to be a way to promote the city. Some of the cities in the world have strong branding because they are made following the identity of the city. The research problems in this research are what visual elements were included in the Palembang city logo; this paper aims to identify the cultural aspect of each component contained in the Palembang city logo by using the theory of logo. This research was using a case study analysis and descriptive qualitative research. Based on the review of the logo and tagline from the Palembang city logo, in conclusion, Palembang city branding has already completed the elements of a good logo such as Persuasive, Harmonious, Supporting a local culture, Must be supporting local Culture. The real situation of the city was designed in original Distinctive. There are several cultural influences represented by the logo. Chinese and Japanese cultural influences have an essential role in the logo of the city branding Palembang.